2017
DOI: 10.1016/j.gene.2017.06.003
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA profiling in kidney disease: Plasma versus plasma-derived exosomes

Abstract: Liquid biopsies have advanced rapidly in recent years for use in diagnostic and prognostic applications. One important aspect of this advancement is the growth in our understanding of microRNA (miRNA) biology. The measurement of miRNAs packaged within exosomes, which are constantly released into the blood stream, may reflect pathological changes within the body. The current study performed miRNA profiling using plasma and plasma-derived exosome samples from two animal models of kidney disease, the 5/6th partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 42 publications
(48 reference statements)
2
47
0
Order By: Relevance
“…In summary, our results suggest that the two materials represent distinctive snapshots of the disease taken from two different points of view and may not be replaced by one another. This is in agreement with the results of another study comparing miRNA content in total plasma and plasma-derived exosomes in kidney disease [37]. The authors showed that miRNAs in plasma and in exosomes are differentially regulated and thus the measurement of exosomal miRNAs cannot be replaced by the measurement of miRNAs in plasma, or vice versa [37].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In summary, our results suggest that the two materials represent distinctive snapshots of the disease taken from two different points of view and may not be replaced by one another. This is in agreement with the results of another study comparing miRNA content in total plasma and plasma-derived exosomes in kidney disease [37]. The authors showed that miRNAs in plasma and in exosomes are differentially regulated and thus the measurement of exosomal miRNAs cannot be replaced by the measurement of miRNAs in plasma, or vice versa [37].…”
Section: Discussionsupporting
confidence: 87%
“…Other studies also found no significant difference between plasma and exosomal miRNAs from healthy people [36]. On the other hand, differential regulation of miRNA levels between plasma and exosomes in different disease animal models has been described as well [37]. Therefore, it seems that export of sncRNAs into blood circulation may be specifically affected in various disease states.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, it is possible that serum miRNAs that are not included in EVs affected macrophage response. However, this possibility is weakened by the observation that EV miRNA levels do not correlate with the blood miRNA levels (47). In addition, we showed that the cytokine expression in macrophages correlated with EV miR-451a levels (Fig.…”
Section: Role Of Mir-451a Within Extracellular Vesicles In the Bloodmentioning
confidence: 85%
“…Through decades of investigations, thousands of miRNAs have been found in humans and animals, among which a notable proportion of miRNAs are found to be critical in the pathogenesis of various diseases, including cardiovascular diseases [9,10,11,12,13,14]. Moreover, some circulating miRNAs predominantly express in CAD patients [15,16].…”
Section: Introductionmentioning
confidence: 99%